Swaziland : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Swaziland during 1990-96. During 1990-95, the shares of exports and imports of goods and services in GDP averaged 81 percent and 92 percent, respectively. The overall trend in economic growth continued in 1995/96. Real GDP expansion was limited to 2.5 percent, fueled by the manufacturing and services sectors. Although there was no new major investment, several established firms expanded or modernized their operations. In particular, this led to significant improvement in the performance of the wood pulp and sugar industries.